Mengatasi Kecanduan Game Pada Anak Dengan Metode Pengharaman Khamar Dalam Al-Qur’an - Mayyadah, Mayyadah (Musawa: Journal for Gender Studies, 2017)
The method of prohibiting khamar in the Qur'an is a way of educating a society by using a gradual approach. The first stage of the Qur'an provides an overview of the human use of dates and grapes, the second stage, the Qur'an in more detail Describes the advantages and disadvantages of drinking khamar. At these two stages, the Qur'an implements the concept of self-cultivation with logic, similarly on the resolving of game addiction. The stage that can be done by parents is to begin to explain to the child about what benefits and what the losses that children get from the game he played. Parents then make a deal with the child about the consequences of his actions in the form of rewards and punishment.